Pengaruh Pendidikan Kewirausahaan dan Ekspektasi Pendapatan Terhadap Minat Berwirausaha Mahasiswa - Harti Oktarina; Eka Adnan Agung; Sitti Hajar Aswad (Universitas Negeri Makassar, 2020)
This study aims to determine: 1) The Influence of Entrepreneurship Education and Income Expectations on Entrepreneurship Interests in STKIP Pembangunan Indonesia economic education students both partially and simultaneously. The study uses a quantitative approach. The study population was STKIP Pembangunan Indonesia economic education students who had participated in entrepreneurship courses with a sample of 194 students. The method of data collection in this study was using questionnaires. The data analysis technique used is the technique of multiple regression using on SPSS 24. Simultaneous test results show that Entrepreneurship Education and Income Expectations simultaneously influence the Interest in Entrepreneurship in Economic Education in STKIP Pembangunan Indonesia with a significance value of 0.028 < alpha value 0.05. Based on the results of the partial test show that: 1) Entrepreneurship Education influences the Interest of Entrepreneurship with the value of sig. amounting to 0.040 <alpha value 0.05; 2) Income Expectations have an effect on Entrepreneurial Interest with a sig value of 0.021 < alpha value of 0.05.